2019
DOI: 10.5530/jyp.2019.11.33
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Urea-Glycerin Based NADES-UAE for Oxyresveratrol Extraction from Morus alba Roots for Preparation of Skin Whitening Lotion

Abstract: Objective: The oxyresveratrol, polyphenol from Morus alba (Mulberry) roots has been known to have potential skin whitening activities. The application of urea-glycerin-based Natural Deep Eutectic Solvent-Ultrasonic Assisted Extraction (NADES-UAE) method was successful on extraction of polyphenols from plant material. The purpose of this research was to get optimum extraction conditions to enhance oxyresveratrol content and get the best lotion formula based on physical properties evaluation. Methods: The roots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Therefore, the moisturizing ability of hydrogel should also be systematically studied. It is worth noting that glycerin has a strong moisturizing ability, which is widely used in the field of skincare products [38][39][40]. Hence, in our experiment, a certain amount of glycerin was added to the prepolymer solution of the hydrogel to enhance moisture retention.…”
Section: Hydrogel Moisturizing Ability Measurementsmentioning
confidence: 99%
“…Therefore, the moisturizing ability of hydrogel should also be systematically studied. It is worth noting that glycerin has a strong moisturizing ability, which is widely used in the field of skincare products [38][39][40]. Hence, in our experiment, a certain amount of glycerin was added to the prepolymer solution of the hydrogel to enhance moisture retention.…”
Section: Hydrogel Moisturizing Ability Measurementsmentioning
confidence: 99%
“…Previously, it was suggested that urea-glycerol-based NADES was a viable option for extracting oxyresveratrol from M. alba roots [20]. However, to obtain a variety of active compounds with anti-melanogenesis activity from M. alba callus, this study used a choline chloride-glycerol-based NADES.…”
Section: Stilbenoids Content and Anti-melanogenesis Activitymentioning
confidence: 99%
“…A number of studies illustrated that NADES can extract active constituents from Morus alba (Alishlah et al., 2019), Coffea canephora (Yuniarti et al., 2019), and Catharanthus roseus (Dai et al., 2016). The advantages of NADES include its easy application, relatively inexpensive costs, ready-to-use formulation, and biodegradable nature.…”
Section: Introductionmentioning
confidence: 99%